MHD natural convection in a partially open trapezoidal cavity filled with a nanofluid; International Journal of Mechanical Sciences; Vol. 119 - Miroshnichenko I. V.; Sheremet M. A. Mikhail Aleksandrovich; Oztop H. F.; Al-Salem K. (2016, 2016)
Title screen